Students' Attitudes toward the Implementation of Imaginative Re-creation in Responding to Literary Works in Learning English in EFL Context - Muhammad Rifqi; Januarius Mujiyanto; Rudi Hartono; Sri Wuli Fitriati (Universitas Negeri Semarang, 2022)
Teachers usually use literary texts in their English classes. They use such materials to teach reading comprehension but rarely combine them with writing. It is a big challenge for teachers to integrate reading and writing activities in the English classroom. Such action is demanding on the one hand, but it is challenging on the other hand. It is appealing because the teachers will burden much checking the students' reading comprehension and their response writing. It is challenging for teachers and students since it integrates reading and writing. This research was done in the context of English as a foreign language, where one hundred and twenty students of the